Manajemen Rantai Pasok Susu Pasteurisasi Dengan Pendekatan Reverse Logistic - Adhi, Wibisono; Rahayu, Winiati Puji (Sekolah Tinggi Manajemen Transportasi (STMT) Trisakti, 2018)
The purpose of the study is to analyze the scheme of reverse logistics for pasteurization chain marketing management using fuzzy analytical hierarchy process (AHP) approach. The triangular fuzzy was using five classes of classification. The result shows that the scheme could be applied to pasteurization in Indonesia by implementing a unit of milk waste processing. Though developing reverse logistics is important, there is another approach which is more important; risk mitigation for pasteurization. The strategies needed to be done are improving cold chain management for chain marketing management, improving supply and demand planning process, and improving a unit of bioethanol process.